Implikasi Hukum Pendaftaran Atas Tanah Adat (Tanah Dati) Terhadap Pemegang Hak Lainnya - Flauangelia Herisli Wattimena; Jenny Kristiana Matuankotta; Novyta Uktolseja (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Land registration in Indonesia is a government obligation mandated in law No. 5 of 1960 concerning land rights, both for individual land and customary land which is jointly owned land in Ambon is called dati land. Common land or dati land if it is registered by including in the name of one person as the owner, it will have legal implications for other rights holders. The type of research is normative juridical research, while the research approach is the statue approach, conceptual approach and finally the case approach or case approach. The technique of collecting legal materials used in this study was to conduct a literature study. The results of the research in this paper are that other rights holders, such as the dati's children whose names are not listed on the land certificate, are not legally the owners of land rights, so that later if there is a dispute over ownership and control over land among the dati's children, the dati's children do not get legal protection.